The effect of multistrain probiotic supplementation in two doses on iron metabolism in obese postmenopausal women: a randomized trial. Issue 8 (6th August 2019) - Skrypnik, Katarzyna; Bogdański, Paweł; Sobieska, Magdalena; Suliburska, Joanna
Abstract : Multistrain probiotic supplementation may influence iron metabolism in obese postmenopausal female patients. Abstract : Obesity leads to detrimental abnormalities of iron (Fe) metabolism. So far, studies have shown that single-strain probiotic supplementation ameliorates the gut microbiota quality disrupted in the obese and improves Fe homeostasis. The effect of multistrain probiotic supplementation and its dose-dependence in obese postmenopausal women remain unknown. The study aimed to investigate the effect of multistrain probiotic supplementation in two doses on selected parameters of Fe metabolism in obese postmenopausal female patients. Three groups of obese postmenopausal women, 30 subjects each, received nine-strain oral probiotic supplement at a daily dose of 2.5 × 10 9 CFU (LD group), 1 × 10 10 CFU (HD group), or placebo for 12 weeks (ClinicalTrails.gov no: NCT03100162). After the intervention, the hair Fe content was lower in both supplemented groups compared to the baseline, the serum zinc (Zn) concentration was higher in the LD group and lower in the HD group vs. the baseline, and the serum erythroferrone (FAM) concentration was lower in the HD group and serum ferritin (FE) concentration was higher in the LD group vs. the baseline. In the whole study population after the completion of the intervention hair Zn correlated positively with serum HEPC and FAM and negatively with serum FE. Hair Fe correlated negatively with serum FE. It is concluded that multistrain probiotic supplementation may influence iron metabolism in obese postmenopausal female patients.